Synthesis of high-entropy MXenes with high-efficiency electromagnetic wave absorption - Linjing Qiao; Jianqiang Bi; Guandong Liang; Yao Yang; Hongyi Wang; Shaoyin Wang (Journal of Advanced Ceramics, 2023)
High-entropy MXenes, as a new emerging class of materials, possess diverse compositions, unexpected physicochemical characteristics, and great potentials for electromagnetic (EM) wave absorption. Herein, two single-to-few-layer high-entropy MXenes, (Mo0.25Cr0.25Ti0.25V0.25)3C2Tx and (Mo0.2Cr0.2Nb0.2Ti0.2V0.2)4C3Tx, were synthesized for the first time. During the exfoliation and delamination processes, the structural, morphological, and compositional evolutions were analyzed, verifying the successful formation of single-to-few-layer two-dimensional MXene nanosheets. Investigations indicate that with the filling content of only 35 wt%, MXene powder filled composites exhibit high-efficiency EM wave absorption performances. The f-(Mo0.25Cr0.25Ti0.25V0.25)3C2Tx possesses the minimum reflection loss (RLmin) of −45.0 dB with the matching thickness of 1.52 mm and the maximum effective absorption bandwidth (EAB) of 5.6 GHz at 1.65 mm thickness. Also, f-(Mo0.2Cr0.2Nb0.2Ti0.2V0.2)4C3Tx can attain an RLmin of −52.8 dB with the thickness of 1.58 mm and an optimum EAB value of 3.6 GHz at 1.50 mm. The satisfactory EM wave absorption efficiency and bandwidth, thin matching thickness, and low filling content prove the lightweight advantage and great application potential of high-entropy MXenes in EM wave absorption. In this work, the high-entropy strategy is applied to tune the EM wave absorption performances for MXenes. Furthermore, high-entropy engineering is expected to provide control and tunability of many other properties, such as electrochemical, catalytic, and mechanical behaviors.